Analisis Perkembangan Bahasa Anak Sekolah Dasar : di Kelas 3 SDN 02 Cupak Tangah - Salsabilah Afief; Ari Suriani (Universitas Palangka Raya, 2025)
Language development is a crucial aspect of a child's growth and overall development. This study aims to examine the language skills of third-grade students at SD 02 Cupak Tangah, focusing on listening, speaking, reading, and writing abilities. The research employed a descriptive qualitative method through direct observation in the school environment. The findings indicate that both the social environment and peer interactions play a significant role in shaping students' language abilities. Although most students have demonstrated basic reading and writing skills, there are still challenges in using proper and correct Indonesian. Many students tend to use their mother tongue in daily communication and struggle to express ideas effectively during learning activities. Furthermore, there is a notable gap between students who are fluent readers and those who are not, which affects their classroom participation and self-confidence. Based on these findings, it is recommended to implement more contextual learning approaches, apply phonics techniques, and encourage active involvement of both parents and teachers to create a supportive environment for children's optimal language development.